A Decomposition Method of Transient Power-Quality Waveforms Combining IHC-HHT and SFVS. Issue 9 (28th May 2018) - Ouyang, Jing; Zhang, Libin; Pan, Guobing; Xu, Hongwei; Chen, Jinxin
Abstract: With the application of renewable energy, the power quality is attracting more attention to. Unfortunately, it is difficult to analyze the transient power quality signal. Hilbert–Huang Transform (HHT) analysis has been proven as an effective method, while, the mode mixing cannot be avoided in the procedure, as well as it is difficult to determine the waveform boundary of sudden changes. Aimed at this problem, a novel method combined Statistical Feature Vector Symbol (SFVS) and Iterative Harmonic Compensation HHT (IHC-HHT) is proposed. Firstly, the envelope distribution of transient power quality signal is changed by harmonic compensation, and the frequency-amplitude range of the compensated harmonic signal is determined according to the characteristics of the transient signal. Secondly, the SFVS method is applied to detect the boundary of sudden changes in the waveform, and divide the power quality signal into several stationary parts on the boundary, and then IHC-HHT method is used to decompose each segment to eliminate the mode mixing. Test results show that this method can improve the performance of decomposition as well as inhibit mode mixing effectively.